PARADIGMA PENDIDIKAN INKLUSI DALAM PERSPEKTIF PENDIDIKAN ISLAM: DINAMIKA PADA SEKOLAH ISLAM - Firman Mansir (Tadrib: Jurnal Pendidikan Agama Islam, 2021)
That it is necessary to go through the perspective of Islamic education. Realizing quality education is one of the goals of the Indonesian state, as stated in the preamble of the 1945 Constitution, paragraph 4. In addition, education is also included in a very important component in order to advance a civilization. improve the quality of education.In writing this article using research based on library research or can be referred to as library research. In this literature research, it means using the media for collecting library materials, such as books, journals, articles, and so on that are able to support this research in solving problems. The method is that after the library materials have been collected, an analysis of the various materials that have been found is then carried out in accordance with the problems raised.In the view of Islam and the study of Islamic Education, both the collaboration of Islamic and Western theories all agree that inclusive education does not conflict with Islamic teachings and values. Because the teachings of Islam itself require obligations and opportunities in studying, and require concern for others without discriminating against ethnicity, skin color, flag color differences and others, as well as different human physical conditions. The existence of inclusive education provides equal opportunities for children with special needs and creates conditions or attitudes that are not discriminatory between normal children and children with special needs under one roof, both in Islamic Education Institutions and in various other communities.